2022
DOI: 10.5194/gmd-15-4331-2022
|View full text |Cite
|
Sign up to set email alerts
|

Global, high-resolution mapping of tropospheric ozone – explainable machine learning and impact of uncertainties

Abstract: Abstract. Tropospheric ozone is a toxic greenhouse gas with a highly variable spatial distribution which is challenging to map on a global scale. Here, we present a data-driven ozone-mapping workflow generating a transparent and reliable product. We map the global distribution of tropospheric ozone from sparse, irregularly placed measurement stations to a high-resolution regular grid using machine learning methods. The produced map contains the average tropospheric ozone concentration of the years 2010–2014 wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…We chose machine learning as an alternative method to propose new station locations, which is a task that is also tackled by using an atmospheric chemistry model [42]. Although we show that the number of underrepresented test samples is not a significant issue for the prediction on the test dataset, underrepresented locations become problematic in the case of applying the models to areas outside the AQ-Bench dataset, e.g., in (global) mapping studies [13,41,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose machine learning as an alternative method to propose new station locations, which is a task that is also tackled by using an atmospheric chemistry model [42]. Although we show that the number of underrepresented test samples is not a significant issue for the prediction on the test dataset, underrepresented locations become problematic in the case of applying the models to areas outside the AQ-Bench dataset, e.g., in (global) mapping studies [13,41,43].…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [13] showed that forward feature selection applied on AQ-Bench leads to 31 features. The data split is kept as in AQ-Bench with 60% training (approximately 3300 samples) and 20% validation and test samples (roughly 1110 samples, respectively).…”
Section: Model Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a global observation-based ozone climatology, we apply the CAMS reanalysis product in our analysis. We note that recent studies have explored the fusion of observations and model output to generate surface O 3 products at a global scale (Chang et al, 2019;Betancourt et al, 2022), but these approaches only work well in regions where measurement sites are available. The CAMS reanalysis provides surface concentrations at a scale comparable with our model, and thus avoids uncertainties associated with the spatial representativeness of observations when using measured concentrations.…”
Section: Deep Learning Model Applicationmentioning
confidence: 99%
“…If training datasets don’t themselves contain error uncertainty values, scientists could experiment with Bayesian-style priors that they themselves estimate so that uncertainty can still be properly represented and propagated (e.g., ref. 5 ).…”
mentioning
confidence: 99%